A study of language expressions used as politeness strategies in english refusal business letters - Nguyễn Thị Thảo (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This thesis investigates language expressions denoting politeness strategies collected from 100 English refusal business letters (in which fifty letters from the US and fifty from the United Kingdom ) under the light of Brown & Levinson’s (1987) politeness theory. The data were collected from the websites of the companies, publishers, universities and from the websites where the recipients posted. For the purpose of carrying the study, a mixed quantitative and qualitative method was applied. The data were analyzed according to the frequencies of politeness strategies in terms of positive and negative used by the British and the American. The study found that the number of language expressions used as negative politeness strategies was more than those used as positive politeness strategies with 330 times versus 206 times respectively. The total number of language expressions denoting politeness strategies used by the British was more than those used by the American, accounting for 271 instances (at 50,56 % of the total words/phrases denoting politeness strategies in 100 refusal business letters) compared with 265 instances (at 49,44 % of the total words/phrases denoting politeness strategies in 100 refusal business letters). In term of positive politeness strategies, the American use expressions denoting positive politeness strategies more frequently than the British, accounting for 109 instances (at 20,34 % of the total language expressions as politeness strategies in 100 refusal business letters ) compared with 97 instances (at 18,10% of the total language expressions as politeness strategies in 100 refusal business letters). The study also found that the frequency of negative politeness strategies was higher in the British refusal business letters than those in the American business letters, accounting for 174 instances ( at 52,7 % of the total negative politeness used) compared with 156 instances ( at 47,3 % of the total negative politeness strategies used). However, the American and the British were the same in employing thanks, apologizes and hedges as their most commonly used strategies.